Hospital waste: can we reduce the environmental impact of a large university hospital? - Martini, Murilo; Chiavaro da Fonseca, Rodrigo; Voigt Severiano, Letícia; Iahnke Garbin, Henrique; Flôres da Rosa, Tainá; Klück, Mariza (Clinical and Biomedical Research, 2017)
Introduction: As technology advances, society must reflect on the destination of materials which are no longer needed. Hospital waste requires special attention due to the associated risk of disease transmission and biological accidents. Also, it tends to increase proportionally to the economic development and is associated with increased use of disposable material. The purpose of this study is to analyze the management of hospital waste at the Hospital de Clínicas de Porto Alegre (HCPA) and to evaluate the effectiveness and feasibility of the measures adopted by the institution to mitigate the impact of its waste on the environment. Methods: Observational study with field research. The management of hospital waste is divided into generation, disposal, storage and final destination. Results: Between 2010 and 2015, the HCPA produced 21.4 tons of biological and sharps waste, 23,000 liters of chemical waste and 113,9 tons of solid waste per month. The main improvements include the implementation of a inspection of the hospital’s waste bins every 2 months, a reduction from 29.42% to 2.79% in the rate of inappropriate disposal of hazardous waste, a 313% increase in investments in staff training, the expansion and adaptation of external areas for temporary storage of hospital waste and the collection of more than 1 ton of waste generated by the local community (sharps, X-ray films, kitchen oil, batteries), as well as the establishment of contracts which will guarantee the appropriate treatment of all types of health care waste. Conclusions: These results demonstrate that mitigating the impact of hospital waste on the environment is possible and should encourage the adoption of similar measures at other institutions. Keywords: Health care quality management; environmental management; hospital administration; medical waste